Rum i förändring - Alvarson, Karolina (2008)
By doing a study of Stapelbäddsparken from a gender perspective I have been investigating and analysing physical planning and landscape architectural design. My intention with this thesis is to reflect on what a gender perspective in physical planning means and what kind of consequences and effects it could have on physical planning and outdoor design. Gender is something that is created, moulded and transformed by social and cultural processes. And it also includes a dimension of power concerning the knowledge of the relationships between women and men where the standard in today's society is still men's interests. To implement gender in my analysis of the park I have been observing how the park is used and who is using it. I have also been investigating who's needs and wishes that has been provided for in planning and design. My method for investigating and analysing the park and its social dimensions has included investigations of the spot, interviews, and studying of data concerning the users. A big part of the time for this thesis has also been applied to study youth culture in public places and how gender can be implemented in physical planning. After making my analysis and investigations I have been able to establish that Stapelbäddsparken is dominated by boys and men and that architectural design will not solve this problem alone. It's a interplay between the social dimensions and the physical design of the park. By doing this thesis I've learned that there are "hidden dimensions of power" in public places. And that it is important to reflect up on who is planning and who is financing our public places in order to be able to discover which norms and values that is being implemented in the physical planning and in the architectural design.